Pengaruh Penambahan Monogliserida Minyak Nabati Terhadap Sifat Mekanis Bioplastik Tapioka - Permatasari Putri Benedicta; Sri Sutanti (Program Studi Teknik Kimia, Universitas Pamulang, 2021)
Vegetable oil is oil derived from plants which has been of limited use as a food ingredient and flavor. Examples of vegetable oils are coconut oil and palm oil. In this research, advanced processing technology from coconut oil and palm oil to monoglycerides was carried out. Monoglycerides were then applied to tapioca bioplastic technology. This study aims to determine whether monoglycerides can improve the mechanical properties of tapi-oka bioplastics. Bioplastic mechanical properties parameters include water resistance, tensile strength, percent elongation, and morphology. The research method was carried out with a randomized block design with 2 factors, namely the type of vegetable oil for the manufacture of monoglycerides (palm oil and coconut oil) and the percentage of addition of monoglycerides (0%; 0.2%; 0.4%; 0.6%; 0 , 8%, and 1%). From the results of the study, it was found that the type and percentage of monoglycerides influenced the mechanical properties of tapioca bioplastics. In the treatment the addition of 1% monoglyceride BDPMK and BDPMS produced the best water resistance, namely 23% and 25%. The addition of 0.6% BDPMK and BDPMS monoglycerides resulted in tensile strengths of 0.53 Mpa and 0.26 Mpa. The best elongation results were in the addition of 0.8% BDPMK and BDPMS monoglyceride treatment, namely 3.49% and 1.46%, and BDPMK morphology was smoother than the BDPMS film morphology. From the overall results it can be concluded that monoglycerides can replace the function of vegetable oil, glycerol and emulsifier simultaneously with coconut oil monoglycerides.